2000
DOI: 10.1063/1.126783
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ta antidiffusion barriers on the thermal stability of tunnel junctions

Abstract: Previous work on spin-dependent tunnel junctions based on NiFe/CoFe/Al2O3/CoFe/MnIr reported structural thermal stability upon anneals up to 300 or 320 °C. Above 320 °C, the tunneling magnetoresistance (TMR) starts to decrease, and interdiffusion occurs at the MnIr/CoFe interface. MnIr diffuses into CoFe and reduces its magnetic moment. It was proposed that this mechanism could be partially responsible for the observed loss of TMR, due to the decrease in interface polarization. In this letter, tunnel junctions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…However, thermal stability up to ϳ400-450°C is required to cope with the standard backend process occurring during MTJ integration with a complentary metal-oxidesemiconductor wafer, 5 while the TMR signal usually decreases above 300°C due to the polarization loss of the CoFe top electrode caused by Mn ͑in Mn-X exchange layer͒ diffusion from the pinning layer. [10][11] Recently, thermal stability has been improved up to ϳ380°C (TMRϭ39%) [19][20][21] by the insertion of an FeO x layer of appropriate thickness between the insulating AlO x barrier and the top pinned FM electrode. Low-resistance MTJs are also potential candidates for replacement of spin-valve sensors in read heads, as recording densities move beyond 100 Gbit/inch 2 , provided RϫA is of the order of a few ⍀ m 2 and TMR ϳ20%.…”
Section: ⍀ Mmentioning
confidence: 99%
See 1 more Smart Citation
“…However, thermal stability up to ϳ400-450°C is required to cope with the standard backend process occurring during MTJ integration with a complentary metal-oxidesemiconductor wafer, 5 while the TMR signal usually decreases above 300°C due to the polarization loss of the CoFe top electrode caused by Mn ͑in Mn-X exchange layer͒ diffusion from the pinning layer. [10][11] Recently, thermal stability has been improved up to ϳ380°C (TMRϭ39%) [19][20][21] by the insertion of an FeO x layer of appropriate thickness between the insulating AlO x barrier and the top pinned FM electrode. Low-resistance MTJs are also potential candidates for replacement of spin-valve sensors in read heads, as recording densities move beyond 100 Gbit/inch 2 , provided RϫA is of the order of a few ⍀ m 2 and TMR ϳ20%.…”
Section: ⍀ Mmentioning
confidence: 99%
“…[7][8] MTJs have a basic FM/I/FM structure, where FM are ferromagnetic electrodes and I is an insulating barrier of ϳ1-2 nm in thickness. Most of the research has been undertaken on insulating barriers based on an Al layer which is oxidized after being deposited by either natural oxidation in air, 1 plasma oxidation ͑oxygen glow discharge͒, 2,[9][10][11][12][13][14] or oxidation in pure oxygen. 14 Although the first room-temperature junctions were prepared using natural oxidation of Al in air, 1 it was soon found that plasma oxidation is more reliable for MTJs with high TMR.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The TMR signal usually decreases above 300°C due to the polarization loss resulting from the Mn ͑in Mn-X exchange layer͒ diffusion into the CoFe top electrode. 3,4 In this work, thermal stability for MTJs is improved up to 380°C by the insertion of an iron-oxide layer with appropriate thickness between the AlOx barrier and the top CoFe pinned electrode. This brings MTJs one step closer to full CMOS backend compatibility.…”
mentioning
confidence: 99%
“…But degradation of TMR ratio by thermal annealing process for the fabrication of MRAM device is the harmful problem of MTJs. This thermal degradation is induced mainly by Mn diffusion in standard backend process for metallisation of CMOS circuits which requires annealing in the forming gas at the range of 400-450 • C. Until now, many attempts have been prepared to achieve high thermal stability [3][4][5]. For instance, (1) a very thin Ta antidiffusion barrier was inserted to stop Mn diffusion into Al oxide barrier between MnIr and CoFe layers [3], (2) interposed FePt layer between Al oxide barrier and the ferromagnetic electrode [4], and insertion of FeO x oxide into barrier interface [5].…”
Section: Introductionmentioning
confidence: 99%